Adubação nitrogenada, parcelada ou singular, em pastagem irrigada de Cynodon spp - Matos, Oscar Ivan Tuz (2017)
The objective of the study was to evaluate forage yield, nutritive value, nitrogen fractions and morphogenic characteristics of irrigated nitrogen fertilized on pasture of Cynodon spp. with split or single dose. The experiment was conducted at the Teaching and Research Unit of beef cattle breading of the Federal Technological University of Paraná, Campus Dois Vizinhos, South-West of Paraná. The experimental area was 1.5 ha with pasture of Cynodon ssp. irrigated, subdivided in 18 paddocks of similar areas, with an average of 400 m2. Experimental design was of completely randomized for the evaluation of production, nutritional value, protein fractionation and for the morphogenic characteristics, with three treatments and six repetitions. Treatments evaluated were: 1A: One application, 2A: Two applications and 4A: four applications of N, with intervals of two post-grazing, totalizing the established fraction. Forage evaluations were determined directly by three cuts in pre-and post-grazing to five cm of the soil, adjusted for each month of the year. For the analysis of chemical composition, samples were obtained by the grazing hand-plucked method. The morphogenic characteristics were obtained by the marked tills technique during the rest period. Data of accumulation rate, pregrazing forage mass, leaf mass, stem mass and dead material presented treatment x month interaction (P<0.05). However, no significant differences were observed (P> 0.05) in the nutritional value and total nitrogen fractionation between treatments. The morphogenic characteristics showed a significant difference (P <0.05) for the single and split application in two times. the pasture of Cynodon can be fertilized with 200 kg of nitrogen per hectare in single dose without interference on nutritional value and without alterations in the protein fractions and superior results in the morphogenic characteristics.